Heavily Yb-doped phosphate fiber with hexagonal inner cladding prepared by the stack-and-draw method. (4th February 2015) - Wang, Longfei; He, Dongbing; Hu, Lili; Chen, Danping
Abstract: The stack-and-draw method was first used to fabricate a heavily Yb-doped phosphate glass double-clad fiber with non-circular inner cladding. An output power of 11.1 W was extracted with slope efficiency of 51.2% from the fiber with 53 cm length. In addition, we also obtained a ~ 2.1 W output power from a fiber with the length ~9 cm.